Selective DDoS Attacks in Application server and Wireless Network – Survey - Kaur, Harpinder; Kaur, Bikrampal (International Journal of Computer Sciences and Engineering, 2025)
In the current computer world, preserving the information is very difficult. Some interrupts can occur on the local organization or network based system. Without security measures and controls in place our data might be subjected to an attack .Now a day’s numerous attacks are evolve. The Dos attack is the most popular attack in network and internet.This kind of attack ingests a large amount of network bandwidth and occupies network equipment resources by flooding them with packet from the machinesdispersed all over the world. Dos attacks are usually doing by following methods: 1) Send unlimited quantity of packets to the server.2) Implementing malwares.3) Teardrop attack.4) Application level flood. A DDos attack is propelled by a mechanism called Botnet through a network of controlled computers. Distributed denial of service (DDos) attack has been regularly in the works attacks that badly intimidate the stability of the internet. In accordance to CERT coordination center, there are mainly three categories of DDoS attacks: flood attacks, protocol attack and logical attack.